The Constitutional Development of Slovakia - Erdősová, Andrea (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter covers the history of the constitutions of previous state forms of what we recognise today as the Slovak Republic from the end of World War I and also mentions the antecedents of the present country.We hold these truths to be self-evident, that all men are created equal, that they are endowed by their Creator with certain unalienable Rights, that among these are Life, Liberty and the pursuit of Happiness. That to secure these rights, Governments are instituted among Men, deriving their just powers from the consent of the governed. (Declaration of Independence)Jefferson’s words remain as true today as they were 250 years ago. The guiding principle of this experiment in a representative democracy is that the government derives its powers from those it governs, but nothing is guaranteed, and people are promised nothing if they do not stand up and force the government to uphold that principle. It seems to be extremely difficult to pinpoint all the essential details of the constitutional development of Slovakia1 because, after the First World War, this development was accompanied by many different turbulences. We must imagine the whole history threat from the great economic crisis through World War II, the era of communism, the development after the Velvet Revolution in 1989 as well as many changes in governments and thus changes in the country’s orientation and in the system of constitutional changes. In the following text, we therefore focus on those moments of constitutional development and constitutional changes that we consider to have had an impact on the current form of the constitution of Slovakia and the constitutional acts and the findings of the Constitutional Court of the Slovak Republic.Law and justice are not available to the legislator. The idea that the legislator can arrange everything according to his will would mean a return to the spiritual position of worthless legal positivism, which has long been obsolete in legal science and practice.3KEYWORDS: constitutional development, the Velvet Revolution, the Constitution of the Slovak republic, abortion finding, the material core of the constitution, Mečiar´s amnesty.